Application of Electronic-Student Worksheets Based on a Scientific Approach to Train Students' Critical Thinking Skills of Bryophytes Material - Ariska, Della Ayu; Indah, Novita Kartika (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2024)
Critical thinking is an essential skill that students must have in the 21st century. The scientific approach is able to train students to think critically. This research aims to describe the implementation of E-LKPD based on a scientific approach, implementation of learning, students' critical thinking skills, and students' responses. This research is referred to as quasi-experimental research. In this research, a "one group pre test and post test design" was used. The sampling process was carried out using a purposive sample technique. A total of 69 students in classes X IPA 2 and X IPA 3 were the research samples. The data collection techniques used are implementation observation techniques, test techniques, and questionnaire techniques. Data analysis was carried out by analyzing research instruments, namely learning implementation sheets, improving students' critical thinking skills, and analyzing student responses to learning implementation. The essential indicators of thinking that are trained are interpretation, analysis, and explanation—increased student learning outcomes from pre-test to post-test with average N-Gain scores for classes X IPA 3 and X IPA 2 respectively of 0.87 and 0.85 in the high category. The implementation of learning with E-LKPD based on a scientific approach in classes X IPA 2 and the implementation of E-LKPD obtained an average percentage of 100%, which shows that student activity when participating in learning using E-LKPD is categorized as very practical for training students' critical thinking skills. Student responses respectively obtained a response percentage of 95% and 94% in the outstanding category.